Fairy tale films: visions of ambiguity - Greenhill, Pauline, editor; Matrix, Sidney Eve, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2010)
In this, the first collection of essays to address the development of fairy tale film as a genre, Pauline Greenhill and Sidney Eve Matrix stress, the mirror of fairy-tale film reflects not so much what its audience members actually are but how they see themselves and their potential to develop (or, likewise, to regress). As Jack Zipes says further in the foreword, "Folk and fairy tales pervade our lives constantly through television soap operas and commercials, in comic books and cartoons, in school plays and storytelling performances, in our superstitions and prayers for miracles, and in our dreams and daydreams. The artistic re-creations of fairy-tale plots and characters in film--the parodies, the aesthetic experimentation, and the mixing of genres to engender new insights into art and life--mirror possibilities of estranging ourselves from designated roles, along with the conventional patterns of the classical tales." Here, scholars from film, folklore, and cultural studies move discussion beyond the well-known Disney movies to the many other filmic adaptations of fairy tales and to the widespread use of fairy tale tropes, themes, and motifs in cinema.--Provided by publisher. To set the field: fairy tales are traditional or literary fictional narratives that combine human and non-human protagonists with elements of wonder and the supernatural. Scholars of literature and film explore how such narratives manifest in film, either native to it or changelings from written literature or oral tradition. Among the topics are the commodification of childhood in contemporary fairy tale film, Guillermo del Toro's Pan's Labyrinth/El Laberinto del fauno and neomagical realism, feminism and place in The Juniper Tree, patriarchal backlash and nostalgia in Disney's Enchanted, feminist cultural pedagogy in Angela Carter and Neil Jordan's The Company of Wolves, and a secret midnight ball and a magic cloak in Stanley Kubrick's Eyes Wide Shut.
Foreword: Grounding the spell: the fairy tale film and transformation / Jack Zipes -- Introduction: Envisioning ambiguity: fairy tale films / Pauline Greenhill and Sidney Eve Matrix -- Mixing it up: generic complexity and gender ideology in early twenty-first century fairy tale films / Cristina Bacchilega and John Rieder -- Building the perfect product: the commodification of childhood in contemporary fairy tale film / Naarah Sawers -- The parallelism of the fantastic and the real: Guillermo del Toro's Pan's labyrinth/El Laberinto del fauno and neomagical realism / Tracie D. Lukasiewicz -- Fitting the glass slipper: a comparative study of the princess's role in the Harry Potter novels and films / Ming-Hsun Lin -- The shoe still fits: Ever after and the pursuit of a feminist Cinderella / Christy Williams -- Mourning mothers and seeing siblings: feminism and place in The juniper tree / Pauline Greenhill and Anne Brydon -- Disney's Enchanted: patriarchal backlash and nostalgia in a fairy tale film / Linda Pershing with Lisa Gablehouse -- Fairy tale film in the classroom: feminist cultural pedagogy, Angela Carter, and Neil Jordan's The company of wolves / Kim Snowden -- A secret midnight ball and a magic cloak of invisibility: the cinematic folklore of Stanley Kubrick's Eyes wide shut / Sidney Eve Matrix -- Tim Burton and the idea of fairy tales / Brian Ray.
Keywords: Fairy tales in motion pictures; Fairy tales -- Film adaptations